A study of physical fitness characteristics of junior wushu players depend on sex difference - Endang Rini Sukamti; Ratna Budiarti; Wisnu Nugroho; Yulvia Miftachurochmah; Kaukab Azeem (Jurnal Keolahragaan, 2022)
Physical fitness was an activity or exercise that can accelerate regeneration when performing several exercises or training. This study aimed to examine the physical fitness characteristics of male and female junior wushu players, followed by determining physical performance differences between both groups. The analytical observational study method was implemented to conduct this study using a cross-sectional approach Fifty junior wushu players (male: n= 25, height= 147.78 ± 12.96 cm; female: n= 25, height= 147.78 ± 12.60 cm) participated in this study by conducting some physical fitness tests. The results showed significant differences in the indicators of 20-meters running with a P-value of 0.049, backbend with a P-value of 0.000, and vertical jump P-value of 0.021. Meanwhile, there was no significant difference between male and female wushu players in the T-test, push up, sit up, dan sit reach (P0,05). From the results, it can be said that male players have higher scores in terms of weight, height, speed, and power, while female players have higher scores in terms of flexibility. This study concluded that it can be taken into consideration to optimize training and testing procedures for junior wushu players.